Faktor yang Berhubungan dengan Aktivitas Manajemen Keselamatan Pasien oleh Perawat Klinis - Agustina, Clara; Putra, Kuswantoro Rusca; Fevriasanty, Fransiska Imavike; Kusumaningsih, Amalia (Poltekkes Kemenkes Bandung, 2026)
Background: Nurses play a critical role in preventing patient safety incidents through the implementation of patient safety management activities. However, evidence on the individual and organizational factors related to these activities among clinical nurses in Indonesian hospitals remains limited. Objective: This study aimed to identify factors associated with patient safety management activities among clinical nurses. Methods: This cross-sectional study was conducted in three hospitals in Malang Raya, East Java, Indonesia, involving 225 nurses recruited using proportional quota sampling. Data were collected using the Nurse Professional Competence Scale, the Practice Environment Scale of the Nursing Work Index, the Safety Motivation Tool, and the Safety Care Activity Scale. Data analysis included descriptive statistics, bivariate analysis (Mann-Whitney test, Kruskal-Wallis test, and Spearman correlation), and multiple linear regression. Results: The final regression model indicated that motivation (β = 0.762, p < 0.001) and work environment (β = 0.161, p < 0.001) were significantly associated with patient safety management activities, explaining 68.9% of the variance. Conclusion: These findings highlight the importance of nurse motivation and supportive work environments in strengthening patient safety practices, while providing empirical evidence on the combined role of individual and organizational factors in Indonesian hospital settings.